Ice Wedge Activity in the Eureka Sound Lowlands, Canadian High Arctic - Campbell-Heaton, Kethra (Université d'Ottawa / University of Ottawa, 2020)
Polygonal terrain underlain by ice wedges (IWs) are a widespread feature in continuous permafrost and make up 20-35%vol of the ground ice in the upper few meters of permafrost. Despite the numerous contemporary studies examining factors that control ice wedge cracking, development and degradation, relatively few have explored ice wedge activity in relation with past climate and vegetation conditions. In the Eureka Sound region, ice wedge polygons dominate the permafrost terrain. Their degradation has started to occur, leading to growth of thaw slumps. The objective of this study is twofold, the principal objective is to investigate the timing of ice wedge activity in the Eureka Sound region using the ¹⁴CDOC dates. The second objective is to evaluate the use of ice wedges as paleotemperature proxies. In July 2018, four ice wedges were sampled at 3-4 depths with each core sample being ~1m in length. In the following summer, eight ice wedges were sampled from the surface, 3-5 core samples were extracted per wedge. Active layer and snow samples were also recovered. Laboratory analyses on the ice wedge samples includes dissolved organic carbon content (DOC) and δ¹³CDOC, radiocarbon dating of DOC, geochemical concentration, and stable water isotopes. The DOC and geochemical results show that snowmelt is the main moisture source for ice wedges in the Eureka Sound region with a minor contribution of leached surface organics. The age (¹⁴CDOC) and size of the studied ice wedges were compared against a cracking occurrence model developed by Mackay (1974), these ice wedges align well with this model and suggest that ice wedge growth is non-linear. Ice wedges in the Eureka Sound region were active during the early to late Holocene (9-2.5 ka). The majority of the activity occurred in the later stage of the early Holocene following regional deglaciation and marine regression. ¹⁴CDOC, high resolution δ¹⁸O and D-excess suggests the occurrence of peripheral cracking in both large and small ice wedges. Rayleigh-type isotopic fractionation was found to occur with depth. As well, post depositional isotopic modification of snow and snowmelt accounts for up to a 4‰ difference of δ18O in surface ice wedge samples. δ¹³CDOC of surface ice wedge samples suggest a habitat transition during the late Holocene from dry meadows to polygonal terrain and the geochemical composition of ice wedges closely reflects that of glacial ice core records.
Keywords: Ice wedge; Permafrost; Paleotemperature Proxy; Geochemistry; Ground ice; Holocene